Design Analysis of Trash Bin with Pull-Push System for Environmental life services Workers (Case Study: Street Sweeper) - Rosyadi, Amarulloh Bagus; Ramadhan, Ali (Intitute of Computer Science (IOCS), 2025)
Design is a planning process in creating objects or systems, including trash cans that function as temporary waste containers. With technological developments, innovation in design has become very important to increase efficiency and user comfort, especially for Environmental life services workers such as street sweepers. Push-pull trash cans have helped mobility and waste management, but still have weaknesses related to time and energy efficiency, such as impractical lid mechanisms, and difficulties when loading waste with a dustpan. qualitative method in this study was used to analyze the Trash bin with push-pull system for Environmental life services Workers in order to obtain information regarding the advantages and disadvantages of its use by street workers. This condition adds to the burden on workers who are already facing health risks due to a lack of personal protective equipment. Therefore, in-depth analysis is needed to evaluate and design a more efficient and ergonomic push-pull bin design, to support the tasks of street sweepers and create a more productive and safe work environment